TREATMENT OF FUNCTIONAL GASTROINTESTINAL DYSPEPSIA - Azimova Movlyuda Makhmudovna (Galaxy International Interdisciplinary Research Journal, 2023)
ABSTARCT Prokinetic drugs (prokinetics) are drugs that enhance and coordinate muscle contractions of the gastrointestinal (GI) tract, including coordination between different intestinal segments, thereby increasing the movement of intraluminal contents. The review considers modern approaches to the use of prokinetics in the treatment of motor disorders of the gastrointestinal tract. The results of studies of various classes of drugs that have a prokinetic effect and target various pathophysiological mechanisms, including impaired antroduodenal coordination, manifested by subjective symptoms and an objective delay in gastric emptying, are presented. Currently used in clinical practice and registered in Uzbekistan, the drug domperidone still remains relevant: in the treatment of patients with functional dyspepsia, gastroparesis and gastroesophageal reflux disease, it is recommended to take it in combination with proton pump inhibitors. Domperidone has an antiemetic effect and a favorable safety profile when used for its registered indications.